Medical leadership arrangements in English healthcare organisations: Findings from a national survey and case studies of NHS trusts. (November 2013) - Dickinson, Helen; Ham, Chris; Snelling, Iain; Spurgeon, Peter
This project sought to describe the involvement of doctors in leadership roles in the NHS and the organisational structures and management processes in use in NHS trusts. A mixed methods approach was adopted combining a questionnaire survey of English NHS trusts and in-depth case studies of nine organisations who responded to the survey. Respondents identified a number of challenges in the development of medical leadership, and there was often perceived to be an engagement gap between medical leaders and doctors in clinical roles. While some progress has been made in the development of medical leadership in the NHS in England, much remains to be done to complete the journey that started with the Griffiths Report in 1983. We conclude that a greater degree of professionalism needs to be brought to bear in the development of medical leadership. This includes developing career structures to make it easier for doctors to take on leadership roles; providing training, development and support in management and leadership at different stages of doctors' careers; and ensuring that pay and other rewards are commensurate with the responsibilities of medical leaders. The time commitment of medical leaders and the proportion of doctors in leadership roles both need to increase. The paper concludes considering the implications of these findings for other health systems.